Screening of the in vitro antileishmanial activities of compounds and secondary metabolites isolated from Maytenus guianensis Klotzsch ex Reissek (Celastraceae) chichuá Amazon - Dionatas Ulises de Oliveira Meneguetti; Renato Abreu Lima; Fernanda Bay Hurtado; Guilherme Matos Passarini; Sharon Rose Aragão Macedo; Neuza Biguinati de Barros; Flávio Augusto de Souza Oliveira; Patrícia Soares de Maria de Medeiros; Júlio Sancho Linhares Teixeira Militão; Roberto Nicolete; Valdir Alves Facundo (Revista da Sociedade Brasileira de Medicina Tropical)
Abstract INTRODUCTION Maytenus guianensis is a member of the Celastraceae family that is used in traditional medicine, particularly for its anti-parasitic and anti-cancer effects. To explore the ethnopharmacological potential of this plant, the present study was designed to screen the in vitro antileishmanial activities of extracts and compounds isolated from M. guianensis. METHODS Maytenus guianensis stems and leaves were extracted in acetone, followed by the preparation of eluates and isolation of secondary metabolites using chromatography on a glass column with silica gel as the fixed phase. The chemical components were identified using spectroscopic methods, including one- and two-dimensional nuclear magnetic resonance of hydrogen-1 and carbon-13, mass spectroscopy, and infrared spectroscopy. The anti-Leishmania amazonensis activities of these eluates and compounds were evaluated by direct promastigote counting and viability assays. RESULTS It was found that the hexane bark eluate produced the strongest anti-L. amazonensis effect, with 90-100% inhibition of the promastigote form. The isolated metabolite that produced the best result was tingenone B, followed by a compound formed by the union of tingenone and tingenone B (80-90% inhibition). CONCLUSIONS Maytenus guianensis shows anti-parasite activity that warrants further investigation to determine the mechanisms underlying this antileishmanial effect and to evaluate the pharmacological potential of these eluates and isolated secondary metabolites, while minimizing any adverse effects.